Composition of biogenic VOCs emitted from select plant species near Cataract Scout Park, Australia, taken during the COALA-2020 campaign - Malcolm Possell; Danica Parnell; Alex Guenther; Jhonathan Ramirez-Gamboa; Hamish McDougall; Clare Paton-Walsh; Jack B Simmons (PANGAEA, 2022)
Measurements of volatile organic compounds composition were captured using thermal desorption tubes from a Teflon enclosure. Measurements were taken at Cataract Scout Park, Appin, N.S.W. (34°14 extquotesingle42.29S 150°49 extquotesingle24.97E) as part of the Characterizing Organics and Aerosol Loading over Australia (COALA-2020) campaign. Enclosures captured branches of select local tree/shrub species. Branch level VOC samples were made using a custom built, 9L branch enclosure. The two ends of the chamber were made from polytetrafluoroethylene (PTFE) supporting a transparent enclosure made from polyvinyl fluoride film (Dupont Chemicals, Macquarie Park, NSW, Australia). Ambient air, passed through an activated charcoal scrubber, was supplied to the chamber at 12 L min-1 using a mass flow controller (Aalborg, Orangeburg, NY, USA). Temperatures inside and outside the chamber were recorded manually every 5 minutes using a Digitech thermocouple thermometer with type K thermocouples (Jaycar Electronics, Rydalmere, NSW, Australia). Photosynthetically active radiation (PAR; μmol m-2 s-1) was recorded at the top of the chamber manually every 5 minutes using an Asensetek Lighting Passport; Asensetek, Taipei, Taiwan). VOCs were collected from the enclosures using a sorbent tube containing Tenax TA (Markes International Ltd, Llantrisant, U.K) connected to an air pump (AirChek 2000; SKC Inc., Eighty-Four, PA, USA) flowing air at 200mL min-1 for 30 minutes. Branches were allowed 30 minutes to acclimate to conditions within the enclosure before VOC sampling commenced. Background (control) enclosure samples were taken at the beginning and end of each day. Post-sampling, tubes were maintained at 4°C until analysis by GC-MS. Sampling occurred over a two-week period in January 2020 and again in March 2020. Sorbent tubes were analysed by thermal desorption GC-MS using the same equipment and protocols described in Lawson et al. (2020; doi:10.3389/fmars.2020.00106). GC-MS data was then post-processed as described in Lawson et al. (2020) except contaminants were subtracted using mean plus 95% confidence values. Peaks were identified by manually comparing mass spectra against a commercial library (NIST08 library in NIST MS Search v.2.2f; NIST, Gaithersburg, MD, United States) using a match factor of 700. When peaks could not be identified, these were labelled using the format UNK with the number that follows being the retention time of the compound. Values for the peaks are expressed as percentages of the total quantifiable peak area (%TQPA).